2017
DOI: 10.5152/eurasianjmed.2016.0060
|View full text |Cite
|
Sign up to set email alerts
|

Cataract Surgery and Possible Complications in Patients with Pseudoexfoliation Syndrome

Abstract: Objective: The aim of this study was to evaluate the demographic characteristics and intraoperative complications of cataract surgery in patients with pseudoexfoliation syndrome (PEX). Materials and Methods:Cases of 225 eyes (80 eyes with pseudoexfoliation and 145 eyes without pseudoexfoliation as the control group) that underwent phacoemulsification cataract surgery and IOL implantation at the Silifke State Hospital Ophthalmology Clinic between April 2011 and April 2013 were analysed retrospectively. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Pseudoexfoliation (PEX) syndrome is described as an age-related disorder in which abnormal fibrillary extracellular material from the lens and iris pigment epithelium gradually accumulates on ocular tissues. 1 Knowledge of the pseudoexfoliation syndrome has existed for decades, as Lindberg focused in detail on it in his doctoral thesis more than 100 years ago. 2 Since then, there has been considerable advancement in understanding its pathogenesis and resulting clinical implications.…”
Section: Introductionmentioning
confidence: 99%
“…Pseudoexfoliation (PEX) syndrome is described as an age-related disorder in which abnormal fibrillary extracellular material from the lens and iris pigment epithelium gradually accumulates on ocular tissues. 1 Knowledge of the pseudoexfoliation syndrome has existed for decades, as Lindberg focused in detail on it in his doctoral thesis more than 100 years ago. 2 Since then, there has been considerable advancement in understanding its pathogenesis and resulting clinical implications.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies reported that PEX can be seen more frequently in men, while other studies reported that PEX can be more frequent in women [ 42 , 43 ]. However, many studies have shown that there is no significant relationship between sex and PEX [ 44 ]. There was no significant relationship between sex and PEX frequency in this present study.…”
Section: Discussionmentioning
confidence: 99%
“…It is usually not determined that a patient has PXF until a secondary outcome is observed, when vision can become impaired, such as PXF co-occurring with glaucoma [ 82 ]. Many cases of PXF are diagnosed during an eye examination, because PXF is considered a risk factor for just not glaucoma, but cataracts as well [ 83 , 84 ]. PXF, on its own, can become problematic if it blocks the trabecular meshwork and leads to elevated ocular pressure [ 81 , 82 , 83 , 84 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many cases of PXF are diagnosed during an eye examination, because PXF is considered a risk factor for just not glaucoma, but cataracts as well [ 83 , 84 ]. PXF, on its own, can become problematic if it blocks the trabecular meshwork and leads to elevated ocular pressure [ 81 , 82 , 83 , 84 ]. PXF can be missed in 20% of eyes that have not been dilated during an ophthalmic exam [ 82 ].…”
Section: Introductionmentioning
confidence: 99%